2018
DOI: 10.1002/psp.2156
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the “parallel lives” thesis: Neighbourhood attachment and residential integration of ethnic minorities in England

Abstract: Recent debates about the failures of multiculturalism have questioned whether ethnic minorities gradually integrate into the British society or instead lead “parallel lives” in segregated communities. Using nationally representative data (2011–2012), we contribute to the debate by investigating the associations between ethnic minority neighbourhood attachment and neighbourhood ethnic composition. Our results show that although all ethnic minorities report higher neighbourhood attachment than White British as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…This implies that, regarding attachment to the city, mixed residential patterns are better than segregated migrant enclaves. This is in stark contrast to general international migration studies and previous neighbourhood research findings (Dekker & Bolt, 2005; Livingston et al, 2010; Putnam, 2007; Wang & Ramsden, 2018). They argued that a neighbourhood composed of diverse ethnicity tends to “hunker down” with lower trust and rarer community cooperation (Putnam, 2007; Stolle, Soroka, & Johnston, 2008), which may cause a weaker sense of attachment (Górny & Toruńczyk‐Ruiz, 2014).…”
Section: Resultscontrasting
confidence: 93%
“…This implies that, regarding attachment to the city, mixed residential patterns are better than segregated migrant enclaves. This is in stark contrast to general international migration studies and previous neighbourhood research findings (Dekker & Bolt, 2005; Livingston et al, 2010; Putnam, 2007; Wang & Ramsden, 2018). They argued that a neighbourhood composed of diverse ethnicity tends to “hunker down” with lower trust and rarer community cooperation (Putnam, 2007; Stolle, Soroka, & Johnston, 2008), which may cause a weaker sense of attachment (Górny & Toruńczyk‐Ruiz, 2014).…”
Section: Resultscontrasting
confidence: 93%
“…Studies found that women of a minority ethnicity are less physically active than women of majority ethnicity [73], thereby infrequently acting as a physically active role model for their children by supporting PA and outdoor play. Additionally, ethnic minority groups more likely live in deprived residential areas [74]. Researchers confirmed that mothers living in a poor neighborhood reported more fears of children’s outdoor play than those from non-deprived residential areas [75].…”
Section: Discussionmentioning
confidence: 99%
“…For Bangladeshis and Black Africans, there is little evidence for generational changes in smoking behavior. One possible explanation could be that both groups may be well protected by their ethnic communities from adopting unhealthy behavior or lifestyles in the host society [9].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the cultures of many migrant-receiving countries such as Britain often emphasize individualism, self-expression, and self-actualization, and are thus more tolerant towards different lifestyles including tobacco smoking, alcohol consumption, and substance use [8]. As first-generation British immigrants grew up and were socialized in their country of origin, their home country cultures could, to some extent, protect them against the host society’s deviant and unhealthy lifestyles [9]. For example, many British first-generation immigrants, especially Pakistanis and Bangladeshis, tend to cluster and concentrate in urban ethnic enclaves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation